Comparative Phytochemical Evaluation of Indonesian Single-Origin Arabica Coffees: Caffeine, Total Phenolic Content, and DPPH Antioxidant Activity - Ahmad Dzaky Mualim; Fitria Puspita (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2026)
Coffee (Coffea arabica) is a globally significant commodity, and Indonesia's diverse archipelagic geography produces beans with distinct origin-associated characteristics. Although the antioxidant properties of coffee are well-documented, the influence of specific geographical origins on its secondary metabolites is less understood. This study aims to investigate the variations in Total Phenolic Content (TPC), caffeine concentration, and antioxidant activity (IC50) across eight prominent Indonesian single-origin Arabica coffees: Aceh Gayo, Ciwidey, Papua Wamena, Bali Kintamani, Kerinci, Toraja, Bajawa, and Temanggung. Utilizing standardized medium-roast samples and ethanolic extraction, the phytochemical profiles were quantified and statistically analyzed via one-way ANOVA and linear regression. The results revealed significant variations (p < 0.001) across all measured parameters based on geographical origin. High-altitude coffees, specifically from Ciwidey and Papua, exhibited the highest TPC (up to 42.72 mg GAE/g) and the most potent antioxidant activity (IC50 of 40.15 ppm and 44.90 ppm, respectively). Conversely, Temanggung coffee, cultivated at lower elevations with nutrient-rich volcanic soil, demonstrated the highest caffeine concentration (1.31%) but the lowest TPC and antioxidant capacity. A strong linear correlation (R2 = 0.793) between TPC and antioxidant activity confirms that phenolic compounds are the primary drivers of radical scavenging efficacy. Ultimately, this study demonstrates that geographical origin significantly shapes the chemical profile and antioxidant capacity of Indonesian Arabica coffees, providing a practical scientific framework for origin authentication and quality evaluation.